The Institutions-Finance-Growth Nexus: The Case Study of EU and European Transition Economies (Journal of Economics, Law and Society, 2024)
This paper empirically investigates the impact of finance and institutions on economic growth using a panel data analysis covering the 2002-2019 period and focusing on three country groups: European Union (EU) member countries, European transition economies, and the overall sample taking all countries together. In contrast to the prevailing view that suggests a positive impact of finance on growth, our findings indicate that finance either decreases growth or is insignificant without evidence of non-linearity. Another finding that comes as a surprise is that institutions play no role in growth either directly or indirectly via finance in all our samples. Our findings, however, support the claim that the finance-growth nexus depends on financial development proxies and the financial and institutional development levels within sample countries.